PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN BIAYA CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN - Arista Pradnyani I Gusti Agung; Nila Rahayu; Adrianda Anwar; Yeldy Dwi Genadi (Jurnal Aplikasi Perpajakan, 2026)
This study aims to analyze the effect of Capital Structure (DER), Profitability (ROA), and Corporate Social Responsibility (CSR) Costs on Firm Value using multiple linear regression analysis techniques. Before testing the hypothesis, a classical assumption test was conducted which included normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure the model met the criteria. Testing was carried out through the F test, t test, and the coefficient of determination (R²). The results showed that the F test with a significance value of 0.032 meant that this research model was worthy of being tested and the Adjusted R² value of 0.541, meaning that 54.1% of the variation in Firm Value could be explained by the model. Partially, DER had no significant effect, ROA had a positive and significant effect, while CSR Costs had no significant effect on Firm Value. Thus, Profitability (ROA) was the most dominant variable in influencing Firm Value.